2008
DOI: 10.1038/nsmb.1437
|View full text |Cite
|
Sign up to set email alerts
|

EGCG redirects amyloidogenic polypeptides into unstructured, off-pathway oligomers

Abstract: The accumulation of beta-sheet-rich amyloid fibrils or aggregates is a complex, multistep process that is associated with cellular toxicity in a number of human protein misfolding disorders, including Parkinson's and Alzheimer's diseases. It involves the formation of various transient and intransient, on- and off-pathway aggregate species, whose structure, size and cellular toxicity are largely unclear. Here we demonstrate redirection of amyloid fibril formation through the action of a small molecule, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

112
1,557
10
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,294 publications
(1,684 citation statements)
references
References 54 publications
112
1,557
10
5
Order By: Relevance
“…In particular, disorder-to-order transitions upon EGCG binding have been observed for the human salivary proline-rich protein IB5 41 and the dephosphorylated form of -casein 42 . Moreover, EGCG has been shown to affect the aggregation pathway of several amyloidogenic proteins 4,[6][7][8] . These studies also suggest that EGCG binds to the protein backbone, as well as to hydrophilic and hydrophobic side chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, disorder-to-order transitions upon EGCG binding have been observed for the human salivary proline-rich protein IB5 41 and the dephosphorylated form of -casein 42 . Moreover, EGCG has been shown to affect the aggregation pathway of several amyloidogenic proteins 4,[6][7][8] . These studies also suggest that EGCG binds to the protein backbone, as well as to hydrophilic and hydrophobic side chains.…”
Section: Resultsmentioning
confidence: 99%
“…The protective effect of EGCG against amyloidosis has been attributed to the formation of off-pathway protein oligomers that prevent fibrillation 6 . The here reported results suggest that formation of these off-pathway species is preceded by a compaction of AS monomers upon EGCG binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG has been shown to inhibit Aβ(1-42) fibrillization by accelerating oligomer aggregation. 19 The oligomerization profile of EGCG showed a sharp increase in Aβ(1-42) oligomerization at 1:5 peptide-to-compound molar ratio ( Figure S2) while taxifolin showed no change in Aβ(1-42) oligomerization. These results agree with the AFM images of Aβ aggregation, which showed that EGCG significantly alters the fibrillization process while taxifolin does not ( Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In EGCG treated flies, however, neurodegeneraton was significantly diminished, indicating that the compound has a protective effect on neurotoxicity in transgenic flies [43]. Intriguingly, EGCG is also a potent inhibitor of α-synuclein and amyloid-β fibrillogenesis, suggesting that it is a generic modulator of protein misfolding and aggregation [44].…”
Section: Identification Of Small Molecules That Influence Polyq-mediamentioning
confidence: 98%